Differential proteomics study of platelets in asymptomatic constitutional macrothrombocytopenia: altered levels of cytoskeletal proteins. (16th July 2014) - Karmakar, Shilpita; Saha, Sutapa; Banerjee, Debasis; Chakrabarti, Abhijit
Abstract Objectives Harris platelet syndrome (HPS), also known as asymptomatic constitutional macrothrombocytopenia (ACMT), is an autosomal dominant platelet disorder characterized by mild‐to‐severe thrombocytopenia and giant platelets with normal platelet aggregation and absence of bleeding symptoms. We have attempted a comparative proteomics study for profiling of platelet proteins in healthy vs. pathological states to discover characteristic protein expression changes in macrothrombocytes and decipher the factors responsible for the functionally active yet morphologically distinct platelets. Methods We have used 2‐D gel‐based protein separation techniques coupled with MALDI‐ToF/ToF‐based mass spectrometric identification and characterization of the proteins to investigate the differential proteome profiling of platelet proteins isolated from the peripheral blood samples of patients and normal volunteers. Results and conclusion Our study revealed altered levels of actin‐binding proteins such as myosin light chain, coactosin‐like protein, actin‐related protein 2/3 complex, and transgelin2 that hint toward the cytoskeletal changes necessary to maintain the structural and functional integrity of macrothrombocytes. We have also observed over expressed levels of peroxiredoxin2 that signifies the prevailing oxidative stress in these cells. Additionally, altered levels of protein disulfide isomerase and transthyretin provide insights into the measures adapted by the macrothrombocytes to maintain their normal functional activity. This first proteomics study of platelets from ACMT may provide an understanding of the structural stability and normal functioning of these platelets in spite of their large size.